On Creative Writing. - Harper, Graeme (New writing viewpoints., 2010)
What is Creative Writing? Millions of people do it, but how do we do it, really? Posing questions about the nature of Creative Writing, this title asks us to consider what Creative Writing actually is, and in doing so encourages us to reflect on how our knowledge of Creative Writing can be increased.